Collaborative Workshop With ICMI On Curriculum Development For Cattle Breeding And Rearing Program Cattle Breeding And Rearing Program - Refika Komala; Resti Fevria; Yulkifli Yulkifli; Rini Elisia; Roni Jarlis; filFildza Arief Syuhada; Farhan Al Azhar Besri (Fakultas MIPA Universitas Negeri Padang, 2026)
Abstract – Variousproblemsfaced by the livestocksector in Indonesia include low quality cattle seeds, inadequate infrastructure, and low productivity. Livestock farmingis generally carried out by rural livestock farmers, managed traditionally as a side business, with a cattle maintenance system that is herded and pennednear the farmer's house. The cattle are left to findtheirownfeed and to meet the shortage of livestockfeed, agricultural waste is provided. The capabilities of cattle farmers are relatively limited, farmers assume that cattle maintenance can bedone as a side job and do not have special technologi calca pabilities. The purpose of the collaborative Workshop with ICMI in Efforts to Increase the Human Development Index through Cattle Breeding and Raisingis to improve participants' knowledge and skills related to modern livestock technology that can increase the productivity and quality of beefcattle. In addition, this workshop alsoaims to strengthen the network and collaboration between experts, practitioners, and related parties in the beef cattle industry in the form of lecture activities on cattle farming and fattening through 16 meetings consisting of 11 courses with expert speakers. The result of this collaboration is an increase in participants' knowledge and skills regarding more effective livestock technology, in order to increase the productivity and quality of beefcattle, especially in Sijunjung Regency.